Designing inclusive educational space for autistic children : a review of the axisting discourse - Rahaman, Farjana; Abdul Rahim, Asiah (2011)
Inclusion of autistic children in the regular educational setting becomes an issue in contemporary discourses on early childhood education. As the enrolment rate of children diagnosed with autism spectrum disorder (ASD) is increasing each year, it becomes crucial for the architects to rethink about their approaches to design inclusive educational learning space to benefit all types of users. While most of the earlier researches addressed the problem of inclusion from educational perspective, a few have been undertaken to address the problem of physical inclusion in terms of school designing. Current researches on design practice for autism friendly learning environment falls mainly in two categories, while the first one addressing the need for special treatment of the environment exclusively for the children with autism spectrum disorder (ASD) (Mostafa, 2008; Mullick & Khare, 2008; Vogel,2008; Paron-Wildes, 2009), the second one actually has translated research based knowledge on this subject matter in to practice thus designing several school building for the target group (Humphrey, 2005; Whitehurst, 2006; Beaver, 2010). This Scenario has left professionals and researchers with new questions regarding the relationship between the need of children with autism and inclusive environment. This paper attempts to critically look into these earlier works based on literature review and hopefully provide inputs to architects to start rethinking in designing Inclusive environment for this special group of children. This could be used as ground to embark on further research to propose appropriate standards for the architects for designing learning environment that reflects inclusion of children with autism spectrum disorder (ASD) along with their able-bodied peers.